Aplicação da membrana de látex natural (NRL) como suporte para cultura das células osteogênicas MC3T3-E1 para regeneração óssea guiada (GBR) - Borges, Felipe Azevedo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The natural rubber latex (NRL) extracted from the rubber tree Hevea brasiliensis is a colloidal system composed of cis-14-polyisoprene polymer. The centrifugation separates the proteins related to allergic reactions, preserving the proteins related to angiogenic activity presented by this material. Their biological applications have grown due to the angiogenic activity and due to its low cost and easy handling. Among its applications, one can mention the release of active compounds (drugs, extracts, nanoparticles, etc.), use as a wound dressing (accelerating the healing of chronic ulcers), vascular prosthesis, etc. It has also been used as a mechanical barrier in guided bone regeneration (GBR), being efficient and accelerating bone healing. Thus, this work aimed a cytotoxicity test of natural rubber latex membrane; producing membranes with different porosities; and assess the adherence of pre-osteoblasts; a mineralization test in the membrane with higher porosity. Cytotoxicity was tested according to the standard ISO 10993-5; the membranes were produced by thermally induced phase separation (TIPS) to provide porosity in the membranes and characterized by scanning electron microscopy with energy dispersive X-ray (SEM-EDS), infrared spectroscopy (FTIR-ATR ) and tensile strength; cell adhesion and morphology of MC3T3-E1 cell subclone 14 was evaluated by SEM-EDS and optical microscopy; mineralization was assessed by MTT, SEM-EDS, FTIR-ATR, alizarin red S, von Kossa staining, and alkaline phosphatase. The membrane was toxic to extract at concentration of100%, but at concentration lower than 80% no longer showed toxicity. All membranes presented irregularities on its surface, with porosity only in those produced at -10°C to -20°C, the latter with higher pores and was tested for mineralization. FTIR-ATR showed no change in the functional groups due to processing and the tensile test showed a typical...

O látex natural (NRL) extraído da árvore seringueira Hevea brasiliensis é um sistema coloidal composto pelo polímero cis-1,4-poliisopreno. Quando centrifugado ocorre a separação das proteínas relacionadas às reações alérgicas, porém permanecem as proteínas relacionadas à atividade angiogênica que este material tem apresentado. Suas aplicações biológicas têm crescido devido à atividade angiogênica e por apresentar baixo custo e fácil processamento. Dentre suas aplicações pode-se citar a liberação de compostos ativos (fármacos, extratos, nanopartículas, entre outros), uso como emplasto (acelerando a cicatrização de úlceras crônicas), prótese vascular, etc. Também tem sido utilizada como barreira mecânica na regeneração óssea guiada (GBR), mostrando-se eficiente e acelerando a cicatrização óssea. Desta forma, este trabalho se baseou em testar a citotoxicidade das membranas de látex natural; produzir membranas com diferentes porosidades; avaliar a adesão de pré-osteoblastos; testar a mineralização celular na membrana com maior porosidade. A citotoxicidade foi avaliada segundo a norma técnica ISO 10993-5 (pelo teste de extração do material); as membranas foram elaboradas segundo a técnica de separação de fases induzida termicamente (TIPS) a fim de proporcionar porosidade nas membranas e caracterizadas por microscópio eletrônico de varredura com energia dispersiva de raio-X (MEV-EDS), espectroscopia no infravermelho (FTIR-ATR) e resistência a tração; a adesão e morfologia celular da célula MC3T3-E1 subclone 14 foi avaliada pelo MEV e microscopia óptica; a mineralização foi avaliada por MTT, MEV-EDS, FTIR-ATR, vermelho de alizarina S, von Kossa e fosfatase alcalina. A membrana foi tóxica para o extrato na concentração de 100%, porém nas concentrações abaixo de 80% já não apresentava toxicidade. Todas as membranas continham irregularidades em sua...
Keywords: Latex; Porosidade; Seringueira; Biocompatibilidade; Regeneração óssea guiada